2000
DOI: 10.1023/a:1017596321472
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Neurons of rat neocortex and spinal cord express NADPH-diaphorase after heterotopic allotransplantation into the sciatic nerve. These peculiarity of diaphorase expression in transplanted cells in comparison with brain cells developing in situ suggest an important role of afferent and efferent relationships in the development of NO mechanisms in neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The former gradually differentiated into GFAP-positive astrocytes, the latter after 30 days formed a multilayer glial lining consisting of vimentin-positive cells at the boundary with tissues of the recipient nerve. The formation of this lining in neurotransplants of the neocortex transplanted into the peripheral nerve has been previously reported by us [6,7,10]. A special study comparing the development of transplants from rat embryonic neocortex in the brain, anterior chamber of the eye, and peripheral nerve showed that this lining consisting of ependyma-like cells is typical only of transplants developing in the nerve [7].…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The former gradually differentiated into GFAP-positive astrocytes, the latter after 30 days formed a multilayer glial lining consisting of vimentin-positive cells at the boundary with tissues of the recipient nerve. The formation of this lining in neurotransplants of the neocortex transplanted into the peripheral nerve has been previously reported by us [6,7,10]. A special study comparing the development of transplants from rat embryonic neocortex in the brain, anterior chamber of the eye, and peripheral nerve showed that this lining consisting of ependyma-like cells is typical only of transplants developing in the nerve [7].…”
Section: Resultssupporting
confidence: 59%
“…The formation of this lining in neurotransplants of the neocortex transplanted into the peripheral nerve has been previously reported by us [6,7,10]. A special study comparing the development of transplants from rat embryonic neocortex in the brain, anterior chamber of the eye, and peripheral nerve showed that this lining consisting of ependyma-like cells is typical only of transplants developing in the nerve [7]. Here we showed immunohistochemically that most cells of the glial lining are presented by ependymocytes: it is known that the ependyma of cerebral ventricles in intact rats contain vimentin [4].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…These data indicate that the microenvironment modulates proliferative activity of transplanted cells. Our previous studies showed that these features are related to the presence of the glial layer at the boundary between the transplant and nerve tissue of the recipient [4]. Environmental factors in the regenerating nerve probably modulate differentiation of several multipotent precursor cells into the glia.…”
Section: Resultsmentioning
confidence: 97%
“…The majority of these cells did not differ from NEC by their morphology. By their maturity they did not reach the level of the neural elements in intact embryonic neocortical transplant (E14) of the corresponding developmental period [6,8]. They could be detected only by immunohistochemical reaction to NeuN (Fig.…”
Section: Resultsmentioning
confidence: 99%